Deeper / 2. - Gordon, Roderick (Tunnels, 2009)
Boy archaeologist Will Burrows wanders the caverns beneath the Colony with his best friend Chester and brother Cal, falls upon the Styx's plan to get rid of Topsoilers with a deadly plague, and risks his life to foil their plot while wondering if his killer stepsister is still on the loose.